Changing patterns of clinical presentation of COVID-19 in hospital admissions: With, or because of, COVID?. Issue 6 (December 2022) - Rafferty, H; Cann, A; Daunt, A; Cooke, G．S
Highlights: In this article we demonstrate the changing nature of COVID admissions from January 2021 to January 2022. In January 2021 most admissions with SARS-CoV2 positive PCR had acute COVID-19 related disease. Comparatively, in January 2022 the majority of admissions had incidental COVID-19. Incidental disease may be related to increasing vaccination rates or change in virulence of the virus with subsequent variants. We suggest monitoring proportion of patients admitted with COVID-19 disease to plan service provision and monitor impact.